Lecturer Protect Rafflesia in L Highlands - The Star, (2008)
Universiti Malaysia Sabah (UMS) senior lecturer Zulhazaman Hamzah has called for the preservation of the habitat of a rare Rafflesia species nemed Kerri found at Lojing Highlands in Gua Musang recently.